Enhanced Stability of All‐Inorganic Perovskite Light‐Emitting Diodes by a Facile Liquid Annealing Strategy. Issue 14 (11th March 2021) - Shi, Jindou; Ge, Wanyin; Tian, Ye; Xu, Meimei; Gao, Wenxing; Wu, Yuanting
Abstract: Ensuring the stability of all‐inorganic halide perovskite light‐emitting diodes (LEDs) has become an obstacle that needs to be broken for commercial applications. Currently, lead halide perovskite CsPbX3 (X = Br, I, Cl) nanocrystals (NCs) are considered as alternative materials for future fluorescent lighting devices due to their combination of superior optical and electronic properties. However, the temperature of the surface of the LEDs will increase after long‐term power‐on work, which greatly affects the optical stability of CsPbX3 NCs. In order to overcome this bottleneck issue, a strategy of annealing perovskite materials in liquid is proposed, and the changes in photoluminescence and electroluminescence (EL) behaviors before and after annealing are studied. The results show that the luminescence stability of the annealed perovskite materials is significantly improved. Moreover, the EL stability of different perovskite LED devices under long‐term operation is monitored, and the performance of the annealed materials is particularly outstanding. The results have proved that this convenient and low‐cost liquid annealing strategy is suitable for large‐scale postprocessing of perovskite materials, granting them stable fluorescence emission, which will bring a new dawn to the commercialization of next‐generation optoelectronic devices. Abstract : A simple liquid annealing strategy is proposed to reduce the photoluminescence loss of perovskite materials under higher temperature condition and to prolong the working stability in light‐emitting diodes devices. The annealed perovskite materials exhibit excellent thermal cycle stability, which will bring a new dawn to the commercialization of next‐generation optoelectronic devices.